2020
DOI: 10.15452/cejnm.2020.11.0004
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of healthcare students and the challenges posed by their clinical learning environment

Abstract: Aim: The aim of the study was to identify the challenges and problems faced by student nurses and paramedic students during the clinical practice stage of their education. Design: The current study utilized a cross-sectional research design. Methods: A sample of 259 students was selected through convenience sampling, comprising 127 student nurses and 132 paramedic students. An adapted self-administered questionnaire, the Clinical Learning Environment Supervision and Nurse Teacher (CLES+T) evaluation scale was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
6
0
2
Order By: Relevance
“…Clinical teachers rarely visit their students on clinical placement due to huge burden on them. 19 This issue can be minimized by hiring an increased number of faculty in the educational institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical teachers rarely visit their students on clinical placement due to huge burden on them. 19 This issue can be minimized by hiring an increased number of faculty in the educational institutions.…”
Section: Discussionmentioning
confidence: 99%
“…[25,26] Others have even reported that supervisors demonstrate good clinical teaching skills. [1,2,9,14,27] In sum, the above attests to a bivalent situation of the quality of clinical supervision. In this context, it is important to identify the strengths and weaknesses inherent in the educational process implemented during the internship to support the trainees in acquiring professional skills.…”
Section: Introductionmentioning
confidence: 89%
“…Elsewhere, these aspects of supervision's development of clinical teaching skills were also often reported as facilitators. [1,2,9,14,27] One of the reasons for this dual situation might be that it is influenced by the state of the teacher's (supervisor's) personal and professional values (caring) and the notion of the teacher's professional identity in the teaching environment. [47] b) About student behavior The literature has also identified barriers to the effectiveness of clinical pedagogical supervision.…”
Section: The Course Of the Internshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Each scenario must be prepared so that the trainer can record routine practices common to most nursing services as well as specific units, such as assessment using a particular assessment tool, appropriate communication, needs analysis, individualized care with elements of transcultural nursing, etc. (Čukljek et al, 2019;Khan et al, 2020;Tomová et al, 2020).…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%